Balloon-assisted tracking technique as 'a way forward' for transradial intervention. Issue 6 (September 2019) - Wojciuk, Jerzy; Beijk, Marcel A.; Goode, Grahame; Brack, Michael; Galasko, Gavin; More, Ranjit; Roberts, David; Eichhöfer, Jonas; Patel, Billal; Chauhan, Anoop; Wiper, Andrew
Abstract : Background: In percutaneous coronary interventions, use of the radial artery may be limited by vascular anatomy or vascular complications, such as radial artery spasm, dissection or perforation. The balloon-assisted tracking (BAT) technique is a novel and innovative method to successfully perform transradial procedures in patients with difficult vascular anatomy, severe tortuosity or radial artery spasm. In addition, the BAT technique can serve as a bail-out technique when vascular complications such as artery dissection or perforation occur. Objective: We analysed data of all percutaneous coronary intervention patients in whom the BAT technique was undertaken in daily practice and report acute and long-term outcomes. Results: A total of 62 patients were included and, in most patients, the BAT technique was performed for radial spasm. Most patients were administered benzodiazepines or nitrates before the BAT technique was performed. The primary end point, defined as successful passage of the catheter through the artery of the arm using the BAT technique, was 98%. 11% of patients developed a complication within 24 h (haematoma, prolonged pain or visible vascular damage at the end of procedure); all completely recovered at follow-up. No complications occurred during long-term follow-up. Conclusion: BAT is a low-risk and easy-to-use technique that increases the success rate of radial artery access and may prevent vascular complications. Abstract : The balloon-assisted tracking (BAT) technique is a novel and innovative method to successfully perform transradial procedures in patients with difficult vascular anatomy, severe tortuosity or RAS. In addition, the BAT technique can serve as a bail-out technique when vascular complications such as artery dissection or perforation occur. We analysed data of all PCI patients (N=62) in whom BAT technique was undertaken in daily practice and report acute and long term outcomes. The primary end point, defined as successful passage of the catheter through the artery of the arm using the BAT technique, was 98%. 11% of patients had a complication within 24 hours (hematoma, prolonged pain or visible vascular damage at the end of procedure), all completely recovered at follow-up. No complications occurred during long term follow-up. BAT is a lowrisk and easy-to-use technique that increases the success rate of radial artery access and may prevent vascular complications.Supplemental Digital Content is available in the text.